STUDI LITERATURE: TANAMAN OBAT HERBAL UNTUK PENYEMBUHAN BATUK DAN FLU - Oashttamadea, Ressa; Maiyonti, Puja (Iris Journal of Health Information Management, 2024)
Coughing is a reflex that is stimulated by irritation of the lungs or respiratory tract. The aim of this research is to determine the benefits of herbal medicinal plants for curing coughs and flu and aims to reveal and convey the types/species of plants used in treating coughs and flu. The method used for literature studies is an article review by searching several national published journals via the database: Google Scholar. The keywords used are "herbal medicinal plants", "cough and flu". Journals published are in the 2020-2024 range (5 years). Full-text research journal: Indonesian Language Journal and produced 6 journals. Next, the inclusion criteria are Indonesian herbal medicinal plants that provide healing effects against coughs and flu. Exclusion criteria, namely plants that can cause allergies or interactions with other drugs. Several herbal medicinal plants can cure coughs and flu. Ginger, known to the public as (Zingiber officinale Roscoe), is a type of plant that is widely used in making medicinal concoctions which people believe can relieve symptoms of colds, flu and coughs.